On Seeing and Being Seen. Some Remarks on the Dimensions of Historical Experience - Bugajewski, Maciej (Sensus Historiae, 2022)
In this article, I analyze the place of historical cognition within the framework of the relationship between the space of experience and the horizon of expectations. I try to understand what a non-objectifying strategy of knowing the past could consist of. It means giving subjectivity to the voices of the past and the status of spectrality. The past, thus recognized, becomes an active factor in the mutual critique of the past and the present.